Teacher professional education coaching to produce high quality lesson plan - Sabilah, Fardini; Abidasari, Erlyna; Husamah, H. (Universitas Muhammadiyah Malang, 2021)
The Teacher Professional Education program (Program Profesi Guru/PPG) equips the teachers’ lifelong teaching skills and improves pedagogical knowledge to lead a successful profession as a teacher. However, the real condition in the SMPN 4 Malang suggested the opposite results, portraying the struggle of some PPG graduates in understanding the K-13 based curriculum, its planning the lesson plan and implementation in their class. This article aims to describe the community service activities teacher professional education coaching to produce high quality lesson plan. The Community Service team reaches out their hands to answer their needs by constructing a coaching and mentoring program in three phases, initiation, implementation and evaluation. Initiation process was done through seminar and focused group discussion, whereas the implementation focused on assisting the revised lesson plan and evaluating the document with the constructed evaluation instrument, then lastly evaluation was done in the microteaching and reflection stage. The results shows that the teachers were already aware of the process standards and content standards of lessons plan, in facts there were still some components that in practice didn’t written properly. Besides, there were also some parts of the lesson plan contents which didn’t match each other. To sum up, after this project, it is highly expected that the PPG graduates’ teachers in SMPN 4 Malang have less difficulties in understanding the government education regulation, in order to plan a more attractive and productive lesson as well as generate self-evaluation tool for further analysis or study. It is suggested to teachers to upgrade their lesson plan by implementing STEAM approach, 4Cs skills and using innovative teaching methods, besides the teachers still need good knowledge and practice in implementing sorts of online teaching platforms.